Bouncing Back: The Psychosocial Benefits of a Community-Based Exercise Program for Children with Non-Severe Burns - Dinithi Atapattu; Victoria M. Shoesmith; Eva Kierath; Mark W. Fear; Fiona M. Wood; Lisa J. Martin (European Burn Journal)
Burns significantly impact children’s physical and psychosocial recovery, even in cases of non-severe injuries, leading to long-term health and mental health risks. This study explores the psychosocial benefits of a community-based exercise program for children recovering from burn injuries, addressing concerns such as anxiety, reduced physical activity, and social challenges. A pre-test–post-test design assessed the effects of an 8-week community-based trampoline exercise intervention on psychosocial outcomes in children and their caregivers. No significant or clinically meaningful physical improvements were observed across measures such as MET score, grip strength, BMI percentile, or heart-rate recovery despite a significant improvement in trampolining performance (p < 0.0001). Psychosocial outcomes showed improved child emotional function (PedsQL, p = 0.024) as reported by parents, though children’s self-reported emotional function and Child PTSD Symptom Scale (CPSS) scores remained unchanged. Parent-reported strengths and difficulty scores for the child remained stable over time but were higher than population norms for hyperactivity and emotional difficulty. Parental post-traumatic stress symptoms decreased significantly over time (p = 0.050), with reductions in avoidance (p = 0.009), hypervigilance (p = 0.007), and intrusion scores (p = 0.026). Children significantly improved their trampolining performance, while parents reported enhanced emotional function for their child. However, children’s self-reports did not reflect these emotional improvements.